Participation in Bauru master plans, Brazil: analysis of the historical evolution of the consultation process - Cavalho Rigitano, Maria; Paceli Barbassa, Ademir (Environnement Urbain / Urban Environment)

(untitled) (Réseau Villes Régions Monde, 2010)
In Brazil, a policy on citizen participation and consultation in urban intervention programs, in particular in the development of master plans, was first introduced into the Federal Constitution in 1988. This article presents an historical reconstitution of Master Plans in Bauru – State of São Paulo – Brazil. The 1968, 1988 and 2005/2006 consultation methods are analyzed using established criteria. The degree of community participation in the processes is estimated by drawing on a typology based on the level of involvement by residents. The effects of participation caused by changes in political regime, technical planning vision, legal support to consultation, recognition of community importance and knowledge acquired during the process are highlighted and discussed.